KLASIFIKASI MAKNA IDIOM PADA ANGGOTA TUBUH BERDASARKAN KAJIAN SEMANTIK - Afrinal Fuadi; Arza Aibonotika; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This Idioms in Japanese are called kanyouku. Kanyouku can be divided based on their forming structure and meaning. This research contains about classificationnow based on the forming structure and meaning of limb idioms. The aim is to find out the classificationnow based on the forming structure and meaning of limb idioms. The data collection method in this study used the literature review method and the note-taking method. The data analysis technique used in this study is based on semantic studies.Keywords: Kanyouku, Idioms, Classification